2018
DOI: 10.1111/imj.13953
|View full text |Cite
|
Sign up to set email alerts
|

Utility of immunohistochemistry for mismatch repair proteins on colorectal polyps in the familial cancer clinic

Abstract: The clinical utility of mismatch repair immunohistochemistry on polyp tissue was low. No additional cases of Lynch syndrome were identified, and a large proportion of patients proceeded to germline testing despite normal polyp immunohistochemistry. We suggest there is no value in this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In agreement, an independent study found that 3.2% (4/125) of advanced adenomas from patients aged <50 years were MMR deficient, leading to an LS diagnosis in 2.4% (3/125) of the cohort [246]. Similarly, 5.3% (3/57) of colorectal adenomas from familial cancer clinic patients were MMR deficient, and germline MMR gene testing of these patients showed that 3.5% (2/57) of the cohort had LS [247]. These yields of LS diagnoses from molecular screening of selected colorectal adenomas are equivalent to universal molecular screening of CRCs, suggesting that young or high-risk patients with colorectal adenomas could be screened for LS following current guidance for CRCs.…”
Section: Msi Analysis Of Cns Tumours Has a Low Sensitivity For Mmr Deficiencymentioning
confidence: 98%
“…In agreement, an independent study found that 3.2% (4/125) of advanced adenomas from patients aged <50 years were MMR deficient, leading to an LS diagnosis in 2.4% (3/125) of the cohort [246]. Similarly, 5.3% (3/57) of colorectal adenomas from familial cancer clinic patients were MMR deficient, and germline MMR gene testing of these patients showed that 3.5% (2/57) of the cohort had LS [247]. These yields of LS diagnoses from molecular screening of selected colorectal adenomas are equivalent to universal molecular screening of CRCs, suggesting that young or high-risk patients with colorectal adenomas could be screened for LS following current guidance for CRCs.…”
Section: Msi Analysis Of Cns Tumours Has a Low Sensitivity For Mmr Deficiencymentioning
confidence: 98%